Role of Homoeopathic Medicines on Inhibition of Serum TSH in Cases of Subclinical Hypothyroidism (Advancements in Homeopathic Research, 2022)
Background: Subclinical hypothyroidism is a common problem with prevalence of 3% to 8% in population without known thyroid disease. Prevalence increases with age and is higher in women. Subclinical hypothyroidism may progress to overt hypothyroidism. Objective:To assess the usefulness of homoeopathic medicines on inhibition of serum TSH in patients of hypothyroidism, a clinical study was conducted at Gaurang Clinic and Centre for Homoeopathic Research, Lucknow, India. Methods: A total of 347 patients have been screened with TSH above 6.0 mIU/L, out of which 202 were found fit for the study. The medicines have been selected on the basis of principles of homoeopathy. Serum TSH was assessed before and after treatment. Results: After comparing pre and post treatment results, the difference in mean values of TSH were 31.91 ± 3.97 vs. 16.69 ± 2.48, improvement=15.23 ± 2.68, t=5.68, p
Keywords: homeopathy; observational study; sub clinical hypothyroidism; TSH; Calcarea carb